INTELLECTUAL CAPITAL VALUATION: METHODS AND THEIR CLASSIFICATION - Ramanauskaitė, Agnė; Rudžionienė, Kristina (Ekonomika, 2013)
Abstract. Currently, a more significant added value is created by intellectual rather than physical capital; yet, according to the current standards of accounting, only a minor segment of intellectual capital is presented in financial accounts of enterprises as it usually does not satisfy one of the criteria of property recognition in financial accounting, namely reliable valuation. As a result, there is an increasing demand for novel methods of valuation, enabling enterprises to establish reliably the value of intellectual capital or its specific segments of a given enterprise. A number of scholars have dealt with the methods of intellectual capital valuation. However, their works analyze and classify different methods of intellectual capital valuation, and different criteria of classification are employed; hence, there is no universally accepted opinion on the issue. That is why the aim of this research was to generalize a scheme of methods of intellectual capital valuation. The main methods applied in the present study are the synthesis and generalization of academic writings, including content analysis. The results of the research and its conclusions are based on the analysis of academic investigations conducted by various authors and the resulting publications. Results. The article generalizes the methods of intellectual capital valuation, suggested by a number of scholars, provides comparisons, reveals the multiplicity of the methods, and highlights the unlimited research of the academic field. Besides, the main classifications of methods of intellectual capital valuation are provided, and the applied criteria are defined. Conclusions. It was established that more than sixty different methods for the valuation of the intellectual capital of an enterprise are available. The results of the research show that these methods are classified according to the four following features. Correspondingly, a classification scheme of intellectual capital valuation methods has been developed. It has been established that most methods of intellectual capital valuation are based on scorecard, they assess specific components; of intellectual capital and in the process of valuation do not employ monetary units of measurement. Tis reveals a lack of the studies that focus on the financial aspect of intellectual capital valuation methods.Key words: intellectual capital, valuation, valuation methods, classification of methods